The Effects of Modifying Agents on the Production of Bioplastic from Sago - Ansanay, Yane O; Waimbo, Korinus N; Haay, Happy A; Kelana, Ardian H; Janah, Tiyas N; Murafer, Yana; Matuan, Merti; Kareth, Hana; Keduman, Wenis; Marani, Margaretha; Rumbewas, Corrnelia; Wamea, Roselin; Raunsay, Ece (International Journal on Food, Agriculture and Natural Resources, 2025)
This study aims to develop sago starch-based bioplastics with the addition of modifying agents such as acetic acid, chitosan, and glycerin to improve mechanical properties, elongation, and biodegradability. The results showed that the optimal combination was reached at 4% acetic acid and 2% chitosan concentration, resulting in the highest tensile strength of 8 MPa, elongation at break of 26%, and degradation rate of 70%. At this condition, the bioplastic matrix has an optimal balance between strength, flexibility, and degradability. Increasing the acetic acid concentration to 6% caused a decrease in tensile strength to 4.2 MPa and elongation at break to 14%, indicating degradation of the matrix structure due to excess acid. Chitosan also affected the mechanical properties, where increasing its concentration from 2% to 4% tended to decrease the elongation at break. The degradation rate tended to increase with higher concentrations of acetic acid, reaching 82% at 6% acetic acid concentration with 2% chitosan, while higher concentrations of chitosan (4%) slowed down the degradation due to a denser and stronger matrix structure. Overall, the combination of sago starch, acetic acid, chitosan, and glycerin produced bioplastics that have improved mechanical properties, water resistance, and environmental friendliness, making them a potential alternative to replace conventional plastics in various industrial applications. These findings support the development of environmentally friendly materials that can reduce the negative impacts to the environment in general and in Papua as the local producer of Sago.